The contribution of transcranial magnetic stimulation in the functional evaluation of microcircuits in human motor cortex - Di Lazzaro, Vincenzo; Ziemann, Ulf (Frontiers in Neural Circuits, 2013)
Although transcranial magnetic stimulation (TMS) activates a number of different neuron types in the cortex, the final output elicited in corticospinal neurones is surprisingly stereotyped. A single TMS pulse evokes a series of descending corticospinal volleys that are separated from each other by about 1.5ms (i.e. ~670Hz). This evoked descending corticospinal activity can be directly recorded by an epidural electrode placed over the high cervical cord. The earliest wave is thought to originate from the direct activation of the axons of fast-conducting pyramidal tract neurones (PTN) and is therefore termed “D” wave. The later waves are thought to originate from indirect, trans-synaptic activation of PTNs and are termed “I” waves. The anatomical and computational characteristics of a canonical microcircuit model of cerebral cortex composed of layer II and III and layer V excitatory pyramidal cells, inhibitory interneurons, and cortico-cortical and thalamo-cortical inputs can account for the main characteristics of the corticospinal activity evoked by TMS including its regular and rhythmic nature, the stimulus intensity-dependence and its pharmacological modulation. In this review we summarise present knowledge of the physiological basis of the effects of transcranial magnetic stimulation of the human motor cortex describing possible interactions between TMS and simple canonical microcircuits of neocortex. According to the canonical model, a TMS pulse induces strong depolarization of the excitatory cells in the superficial layers of the circuit. This leads to highly synchronised recruitment of clusters of excitatory neurons, including layer V PTNs, and of inhibitory interneurons producing a high frequency (~670 Hz) repetitive discharge of the corticospinal axons. The role of the inhibitory circuits is crucial to entrain the firing of the excitatory networks to produce a high-frequency discharge and to control the number and magnitude of evoked excitatory discharg